One day at a time. - Ho, Qi Yi. (2013)
People who suffer from mental illness are often misunderstood as deviants of the society. Amongst the many misconceptions present is that those suffering from mental disorders will never fully recover from the illness, creating a highly problematic and prejudiced standpoint on the matter. Such stigma has resulted in deterioration in condition for many who are battling mental illnesses, creating a vicious cycle that often leads to other health and social problems.